Evaluation of efficacy and safety for compound kushen injection combined with intraperitoneal chemotherapy for patients with malignant ascites: A systematic review and meta-analysis - Yu, Hui-Bo; Hu, Jia-Qi; Han, Bao-Jin; Cao, Hui-Juan; Chen, Shun-Tai; Chen, Xin; Xiong, Hong-Tai; Gao, Jin; Du, Yan-Yuan; Zheng, Hong-Gang (Frontiers in Pharmacology, 2023)
Objectives: Compound Kushen injection (CKI) combined with intraperitoneal chemotherapy (IPC) is widely used in the treatment of malignant ascites (MA). However, evidence about its efficacy and safety remains limited. This review aimed to evaluate the efficacy and safety of CKI combined with IPC for the treatment of MA. Methods: Protocol of this review was registered in PROSPERO (CRD42022304259). Randomized controlled trials (RCTs) on the efficacy and safety of IPC with CKI for the treatment of patients with MA were searched through 12 electronic databases and 2 clinical trials registration platforms from inception until 20 January 2023. The Cochrane risk-of-bias tool was used to assess the quality of the included trials through the risk of bias assessment. We included RCTs that compared IPC single used or CKI combined with IPC for patients with MA schedule to start IPC. The primary outcome was identified as an objective response rate (ORR), while the secondary outcomes were identified as the quality of life (QoL), survival time, immune functions, and adverse drug reactions (ADRs). The Revman5.4 and Stata17 software were used to calculate the risk ratio (RR) at 95% confidence intervals (CI) for binary outcomes and the mean difference (MD) at 95% CI for continuous outcomes. The certainty of the evidence was assessed according to the GRADE criteria. Results: A total of 17 RCTs were assessed, which included 1200 patients. The risk of bias assessment of the Cochrane risk-of-bias tool revealed that one study was rated high risk and the remaining as unclear or low risk. Meta-analysis revealed that CKI combined with IPC had an advantage in increasing ORR (RR = 1.31, 95% CI 1.20 to 1.43, p < 0.00001) and QoL (RR = 1.50, 95% CI 1.23 to 1.83, p < 0.0001) when compared with IPC alone. Moreover, the combined treatment group showed a lower incidence of myelosuppression (RR = 0.51, 95%CI 0.40–0.64, p < 0.00001), liver dysfunction (RR = 0.33, 95%CI 0.16 to 0.70, p = 0.004), renal dysfunction (RR = 0.39, 95%CI 0.17 to 0.89, p = 0.02), and fever (RR = 0.51, 95%CI 0.35 to 0.75, p = 0.0007) compared to those of the control group. The quality of evidence assessment through GRADE criteria showed that ORR, myelosuppression, and fever were rated moderate, renal dysfunction and liver dysfunction were rated low, and QoL and abdominal pain were rated very low. Conclusion: The efficacy and safety of CKI combined with IPC were superior to that with IPC alone for the treatment of MA, which indicates the potentiality of the treatment. However, more high-quality RCTs are required to validate this conclusion. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022304259], identifier [PROSPERO 2022 CRD42022304259].